The design of a service information system at the South Sumatra grilled chicken restaurant in the city of Palembang, the website based on - Andrean Hendri; Zulhipni Reno Saputra Elsi (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
The development of technology is increasingly rapid, In various fields of Information Technology, it is required to be more sensitive to the state of people's lifestyles. The human need for information technology is very necessary because it helps in providing fast and precise information services. To support these information technology services, media or tools are needed, namely computers as tools used to process data according to procedures that have been formulated to simplify and speed up the completion of work. The number of companies that have been established has made sales competition tougher, every sale competing to provide the best quality with sales techniques that are not optimal